Reductive Umpolung and Defunctionalization Reactions through Higher-Order Titanium(III) Catalysis - Streuff, Jan (Synlett, 2022)
The single-electron transfer from an in situ formed titanium(III) catalyst to ketones, imines, nitriles, Michael acceptors, and many other functions has enabled a large number of intra- and intermolecular reductive umpolung reactions. Likewise, it allows the homolytic cleavage of functional groups for selective defunctionalizations. These reactions often take place with the participation of two titanium(III) species, avoiding free-radical pathways and enabling high catalyst control of the reaction selectivity. This account discusses the development of the individual reactions together with the fundamental mechanistic discoveries that led to a better understanding of such titanium(III)-catalyzed processes in general.1 Introduction2 Active Titanium(III) Species and Additives3 Ketone-Nitrile Couplings4 Further Reductive Umpolung Reactions5 Catalytic Homolytic C–CN and C–SO2R Cleavage6 Conclusion
Keywords: catalysis; cleavage; radicals; titanium; umpolung